The impact of dental care of hospitalized children (Research, Society and Development, 2023)
The dentistry professional must have one of the central roles within a multidisciplinary team in the hospital follow up of the child patient, perfoming the supervision and maintenance of oral health, these physiological aspects being of great importance for the growth and development of the child. The present study aims to investigate and inform about the positive impact caused by the insertion of dental practice in the hospital environment, focusing on hospitalized children and adolescents. The sample consisted of 85 children, who at the time of data collection were hospitalized in the hospital wing of the Pronto Socorro da Criança in the south zone (PSC) and in the Instituto da Criança do Amazonas (ICAM), through questionnaires applied to their respective responsible. The results revealed that 52.9% were male and 47.1% were female, the dental health status revealed that 62.8% were in good condition, 26.7% in fair condition and 10.5% in good condition. bad. It was concluded that dental follow-up aimed at hospitalized children, through health promotion actions and preventive procedures, is of great importance for maintaining the child's oral health during the period of hospitalization, since oral health contributes greatly to overall satisfactory health.